Delphi method analysis: The role of regulation in the mobile operator business in Finland - Kimmo Laakso; Anita Rubin; Hannu Linturi (United States, 2022)
Mobile communication has grown out of its previous scope and scale. Mobile operators play a significant role in this phenomenon. Since the mobile operator business is highly regulated, we have analyzed the effects of regulation on the industry. We also have considered the possible effects in the coming years up to 2015. The aim of this paper is to discuss the possibilities of a futures-oriented method - i.e., the Delphi method, to estimate the effect of regulation on the mobile operator business.  The challenge is that the method was originally created to assess experts' opinions about the course of development of a certain technology or phenomenon in the future and then, by using a scenario technique, to draw conclusions about its possible futures. Now the Delphi method is also being used to estimate past development, i.e. experts' opinions of the causes and effects of laws and other regulations in the past few decades. The paper forms a part of a larger study, the aim of which is to analyze the effects of changes in the regulatory framework for the mobile operator industry in Finland. According to this research the ultimate goals of the regulator, set as early as in the middle of the 1980s, have been actualized: In Finland there are several competing nationwide mobile operators and the use of mobile phones is cheap compared to many other countries.
PICMET '10 Proceedings: Technology Management for Global Economic Growth